Effects of obesity and diabesity on heart rhythm in the Zucker rat. (20th February 2021) - Sultan, Ahmed; Jacobson, Michael; Adeghate, Ernest; Oulhaj, Abderrahim; Shafiullah, Mohamed; Qureshi, Anwar; Howarth, Frank Christopher
Abstract: Obesity and type 2 diabetes mellitus are risk factors for hypertension, coronary heart disease, cardiac arrhythmias including atrial fibrillation, heart failure and sudden cardiac death. The effects of obesity and diabesity on heart rhythm were investigated in the Zucker diabetic fatty (ZDF) and Zucker fatty (ZF) compared to the Zucker lean (ZL) control rat. In vivo biotelemetry techniques were used to assess the electrocardiogram and other cardiac and metabolic parameters. ZDF rats were characterized by age‐dependent elevations in fasting and non‐fasting blood glucose, glucose intolerance and weight gain and ZF rats were characterized by smaller elevations in fasting and non‐fasting blood glucose and greater weight gain compared to ZL rats. Heart rate (HR) was progressively reduced in ZDF, ZF and ZL rats. At 195 days (6.5 months) of age there were significant differences in HR between ZDF (265 ± 8 bpm, n = 10), ZF (336 ± 9 bpm, n = 10) and ZL (336 ± 10 bpm, n = 10) rats and significant differences in HRV between ZDF (22 ± 1 bpm, n = 10), ZF (27 ± 1 bpm, n = 10) and ZL (31 ± 1 bpm, n = 10) rats. Power spectral analysis revealed no significant ( P > 0.05) differences in HRV at low frequencies, reduced HRV at high frequencies and increased sympathovagal balance in ZDF compared to ZF and ZL rats. HR was reduced by ageing and additionally reduced by diabesity in the absence of changes in physical activity and body temperature. Reductions in HRV associated with altered sympathovagal drive might partly underlie disturbed HR in the ZDF rat. Possible explanations for reduced HR and future mechanistic studies are discussed.